Temporary Optical Coupler for Optical Cable Re-Routing Without Service Interruption - Takui Uematsu; Takanori Kiyokura; Hidenobu Hirota; Hiroyuki Iida; Tomohiro Kawano; Tetsuya Manabe (IEEE Photonics Journal, 2018)
We design a temporary optical coupler to obtain high injection and extraction efficiencies while keeping the bending loss low with the aim of realizing optical cable re-routing without service interruption. The temporary optical coupler injects/extracts signal lights into/from a fiber by using fiber bending. The extraction efficiency is improved by using a double-clad fiber or a graded-index fiber for light injection and extraction while the injection efficiency is maintained compared with that of a conventional temporary optical coupler that uses a single-mode fiber. This improvement enables us to realize an optical cable re-routing operation support system that requires no service interruption.